AUSENCIA DE REGLAS BÁSICAS EN LA APLICACIÓN DE LA FIGURA JURÍDICA DEL RECONOCIMIENTO DE RESPONSABILIDAD Y PAGO VOLUNTARIO GENERAN DESCONFIANZA EN LA POTESTAD ADMINISTRATIVA SANCIONADORA”. - MENDIETA CAMACHO, FERNANDO JAVIER (2021)
The administrative sanctioning power analyzed in this thesis under the title: "Absence of basic legal rules in the application of the figure of recognition of liability and voluntary payment generate distrust in the sanctioning administrative power", evidences through the conceptual, legal and doctrinal review of the present topic, a legal vacuum existing in the Administrative Organic Code in the figure of recognition of liability and voluntary payment, In which the actions of the public administrations are compromised with respect to the administrated parties, since there is no specific regulation that establishes the correct way in which this figure is to be applied, with these considerations, the incorporation of an administrative regulatory regime based on principles of speed and procedural economy that give 4 legal basis to the existence of the recognition of liability and voluntary payment is foreseen, For this reason, the present analysis and investigation was based on similar legal figures contained in comparative law regulations of countries such as Argentina, Colombia, Spain and Peru, in which there are established a number of rules that should be included in the Ecuadorian legal system, so that, with its incorporation, constitutional rights such as due process, legal certainty and prohibition of self-incrimination are respected, since the foundations contained in the Ecuadorian administrative regulations are not clear and allow both the public administrations as well as the parties involved to erroneously and extensively interpret the spirit of the regulation, distorting it and causing the parties involved to be reluctant to accept the figure in question, since the administrative regulations do not provide them with the certainty or confidence necessary for a correct correlation between these subjects involved in an administrative sanctioning procedure. In order to reinforce the criteria expressed regarding the need to typify the basic legal rules that regulate both the actions of the public administrations and those administered, it was foreseen the application of interviews and surveys that served as a basis to know if the figure of recognition of responsibility and voluntary payment contained or not the specific regulations that regulate its sanctioning activity, The results obtained were clear, specific and favorable to the present investigation, allowing the presentation of a project of legal reform to the Administrative Organic Code and thus guaranteeing the constitutional rights of the administered when they are involved in an administrative sanctioning procedure.